Enriching UNESCO’s Life Skills Through Educational Technology Interventions: Analysis of Interpersonal Life Skills of Distance Learners (Journal of Asian Development Studies, 2025)
Educational technology has a great revolution in all the fields of education. In the field of distance education, educational technology plays a vital role by providing new and cost-effective platforms to make the teaching-learning process efficient, reaching and developing life skills among learners. UNESCO categorized life skills into main three areas cognitive, interpersonal, and intrapersonal skills. In the present study interpersonal skills were focused which aimed to examine UNESCO’s life skills’ development through educational technology interventions, particularly in the context of interpersonal life skills of distance learners of Allama Iqbal Open University (AIOU). The population of the study was B. Ed 4 Years students of which 70 students were randomly selected. Research design was quantitative followed by a survey method. Self-developed research tool was administered, and data was analysed in terms of descriptive statistics. The findings suggest that distance learners using educational technology show strong interpersonal life skills in all the sub-constructs including communication skills, cooperation, conflict resolution, teamwork, respect for others, emotional understanding, problem-solving, and active listening. Comparisons indicated no gender difference indicating that educational technology effectively fosters interpersonal life skills among all distance learners. There was no significant difference in interpersonal life skills based on respondents’ computer literacy levels, job status, and income levels. It is concluded that educational technology intervention develops interpersonal life skills among distance learners. The study recommends that educational technology interventions may be used in all forms of education to enhance the interpersonal life skills of the learners.